Correction: Voluntary sports programs for individuals with mental health disorders: The trainer's view. - Florence Epiney; Frank Wieber; Daniela Loosli; Hansjörg Znoj; Nikolai Kiselev (PLoS ONE, 2024)
[This corrects the article DOI: 10.1371/journal.pone.0290404.].